(untitled) (Central Medical College Journal, 2023)
Background: The most important global cause of mortality is suicide.Global suicide rates have increased 60% in the last 45 years. Unnatural death is one of the indications of social and mental health in a society.It is often neglected by researcher, health professionals, health policy makers and the medical profession.Unnatural death by suicide relates to multiple factors eg. low socio-economic condition, dowry system, lack of education, failure of love, poverty etc. Shooting, hanging and stabbing are a hard way of committing suicide and typically a male choice.Poisoning and drowning are soft way of committing suicide and typically a female choice. This article was aimed to find out the pattern and demography of suicidal death. Materials and method: To find out the pattern of suicidal death, a retrospective data was collected from the records of Forensic Medicine Department in Sir Salimullah Medical College, Dhaka for the period of 1 year from January 2021 to December 2021. Objective: The objective of this study was to find out pattern and demography of suicidal death, its distribution according to age, sex, common method used by victims and in this way try to identify the causative factors and develop the preventive measures that are essential to reduce suicidal death. Results: The commonest methods of committing suicide were found hanging which was 60.3%, followed by poisoning 26%, burn 1.34%. Most of the victims (25%) were from the age group 1-15 years. Out of 328 cases 170 (52%) were male and 158 (48%) were female. Among them 196 (59.8%) were married and 132 (40.2%) were unmarried. Most common poison was Organo Phosphorus Compound (OPC). Conclusion: To reduce the number of suicide a well designed and comprehensive program is needed which will identify the causative factors and which might help in prevention of suicide. Central Medical College Journal Vol 6 No 1 January 2022 Page: 34-38